Neraca Pembayaran dan Neraca Perdagangan Dalam Perspektif Ekonomi Islam di Indonesia - Khairun Nisaa; Kamila Alhalimi; Muhammad Albahi (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to examine the Balance of Payments and Balance of Trade of Indonesia from the perspective of Islamic Economics. The balance of payments is one of the important instruments in a country's economy that reflects international economic relations, while the balance of trade reflects the difference between exports and imports of goods. In the perspective of Islamic Economics, both balances must pay attention to the principles of justice and balance, where foreign transactions are carried out in a way that does not harm either party. This study adopts a qualitative approach with descriptive analysis, using secondary data in the form of reports on the balance of payments and trade of Indonesia and references related to Islamic Economics. The results of the study indicate that the application of Islamic economic principles in the management of Indonesia's balance of trade and payments can improve economic balance and reduce dependence on foreign debt.